The Influence of Depression on Health-related Quality of Life among Patients with Heart Diseases - Hatif Ali Abed, Kareem Reshak Sachet (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Heart disease is the highest cause of death in Europe and the rest of the world. Patients with symptomatic heart disease may benefit from emergency heart disease intervention Aims of the study: assess the Influence of Depression on Health-related Quality of Life among Patients with Heart Diseases Methodology: A descriptive cross-sectional study was carried out from period December 15th, 2021 through May 15th, 2022 at Al-Samawah Teaching Hospital’s Center Coronary Care Unit, and A non-probability (purposive) sample of the study consisted of (100) patients with heart diseases were selected from the Center Coronary Care Unit at Al-Hussein teaching hospital in Sammawa city Results: The results show that (23%) of heart patients were moderate depression. And most heart patients were males. This suggests that depression have a significant influence on quality of life among patients with heart disease. Conclusions : The majority of heart disease patients suffer from moderate depression, and depression have a significant influence on quality of life among patients with heart disease.